PENERAPAN MODEL PENGAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA DI KELAS IV SD NEGERI 023 SEDINGINAN KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Parisman '; Damanhuri Daud Daud; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research is motivated by low yields fourth grade students learn science Sedinginan SDN 023, with a grade average of 57.29. While the value of minimum completeness criteria (KKM) IPA is 65 Among students, amounting to 24 people only 7 students who achieve KKM with classical completeness 29.17%. For that held Classroom Action Research (CAR), which aims to improve science learning outcomes fourth grade students at SDN Academic Year 2013/2014 023 Sedinginan through Application of Direct Teaching Model. The formulation of the problem is whether the application of direct teaching models can improve learning outcomes IPA 023 fourth grade students of SDN Sedinginan Land District of White? The subjects were 023 fourth grade students of SDN Sedinginan totaling 24 people. Data collection instrument in this study were the teacher and student activity sheets and learning outcomes. From the data analysis the percentage increase in the activities of teachers first cycle of 60% the first meeting, a second meeting increased to 70% increase kesiklus II first meeting to 80% and increased again at the second meeting of the second cycle to 90%. While the percentage of student activity in the first cycle the first meeting 60% increase in the second meeting to 75% increase to the first meeting of the second cycle to 80% and increased again at the second meeting of the second cycle to 95%. Then improving student learning outcomes from the first cycle to the base score is an average of 57.29 into 62.91 with a percentage increase of 9.8% and an increase in learning outcomes from the first cycle to the second cycle is an average of 62.91 to 75 , 62 with a percentage increase of 20.20%. The results of the study in class IV SDN 023 Sedinginan prove that the Application Model Jump Teaching science can enhance learning outcomes 023 fourth grade students of SDN Sedinginan Land District of White. Keywords: Models Direct Teaching, Learning Outcomes IPA